MONOPOLI ARAB: INOVASI MEDIA PEMBELAJARAN BERBASIS EDUTAINMENT UNTUK MENINGKATKAN MAHARAH KALAM SISWA MA ISLAMIYAH TANGGULANGIN SIDOARJO - Indi Rohmawati; Najih Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate how effective the use of monopoly learning media is in improving students' speaking skills at MA Islamiyah Tanggulangin Sidoarjo. In this study, the method applied is quantitative with a Quasi Experimental Design through a Control Group Pre-Test and Post-Test approach. The sample studied consisted of students of class XI IPS 1 and XI IPS 2, each of which has 18 students. Class XI IPS 1 acted as an experimental group that utilized monopoly learning media, while class XI IPS 2 acted as a control group that used traditional methods. To collect data, interview techniques, observation, documentation, and implementation of pre-test and post-test were used. Data analysis was carried out using the Kolmogorov-Smirnov normality test, homogeneity test, and Paired Sample T-Test hypothesis testing supported by the SPSS application. The findings of this study indicate that the average pre-test score for the experimental class reached 62.72, then increased to 78.72 in the post-test with a significance value of 0.000 which is smaller than 0.05. Thus, monopoly learning media has been proven to be effective in improving students' speaking skills because it is able to create a pleasant learning atmosphere, increase motivation, encourage active involvement from students, and help students master vocabulary through repeated muroja'ah activities in an interesting game context. This study aims to evaluate how effective the use of monopoly learning media is in improving students' speaking skills at MA Islamiyah Tanggulangin Sidoarjo. In this study, the method applied is quantitative with a Quasi Experimental Design through a Control Group Pre-Test and Post-Test approach. The sample studied consisted of students of class XI IPS 1 and XI IPS 2, each of which has 18 students. Class XI IPS 1 acted as an experimental group that utilized monopoly learning media, while class XI IPS 2 acted as a control group that used traditional methods. To collect data, interview techniques, observation, documentation, and implementation of pre-test and post-test were used. Data analysis was carried out using the Kolmogorov-Smirnov normality test, homogeneity test, and Paired Sample T-Test hypothesis testing supported by the SPSS application. The findings of this study indicate that the average pre-test score for the experimental class reached 62.72, then increased to 78.72 in the post-test with a significance value of 0.000 which is smaller than 0.05. Thus, monopoly learning media has been proven to be effective in improving students' speaking skills because it is able to create a pleasant learning atmosphere, increase motivation, encourage active involvement from students, and help students master vocabulary through repeated muroja'ah activities in an interesting game context.